A Cloud Based Irrigation System for Agriculture - Sathyanarayanan PSV (JOIV : International Journal on Informatics Visualization, 2018)
By 2050, it's normal that the total populace will contact 9.2 billion individuals, 34 percent higher than today. A lot of this development will occur in creating nations like India, which has the biggest zone on the planet with arable land for agriculture. To stay aware of rising populaces and wage development, worldwide sustenance generation must increment by 70 percent so as to have the capacity to encourage the world. With help of IoT, control focuses gather and process information continuously to enable ranchers to settle on the best choices as to planting, treating and collecting crops. Sensors set all through the fields are utilized to gauge temperature and stickiness of the dirt and encompassing air. We Propose a Cloud based Irrigation System for better agriculture farming.